2016
DOI: 10.3109/08820538.2016.1142578
|View full text |Cite
|
Sign up to set email alerts
|

Syrian Civil-War-Related Intraocular Foreign Body Injuries: A Four-Year Retrospective Analysis

Abstract: Despite delays in treatment and the severity of injuries, 82% (64/78) of the eyes had an improvement in VA after the surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In total, 38 publications met the inclusion criteria of this systematic review as shown in Figure 1 10–47. There was no other systematic review on this area of research found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 38 publications met the inclusion criteria of this systematic review as shown in Figure 1 10–47. There was no other systematic review on this area of research found.…”
Section: Resultsmentioning
confidence: 99%
“…Seven papers did not indicate the gender of the casualties 10 11 15 23 26 29 40. Eight papers met the eligibility criteria and had specific data for children aged less than 18 years 12 13 19 24 27 44–46. Nine other papers were excluded due to being specific to childhood trauma 18 30–33 47.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without appropriate diagnosis and treatment, penetrating ocular injury with an intraocular foreign body (IOFB) can lead to blindness or other severe ocular complications [3]. Injuries to the anterior and posterior segments may occur due to ocular trauma, and surgical treatment should be undertaken to reconstruct the anterior and posterior segments [4][5][6][7][8]. Siderosis bulbi, one of the most serious complications, may be caused by retention of an iron-containing IOFB, which can cause deposition of iron molecules in the ocular tissues [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Glass intraocular foreign bodies (IOFBs) complicate up to 14% of all IOFB cases and are especially common with motor vehicle accidents (MVAs) and explosions 1, 2, 3, 4, 5, 6. Up to 70% of MVA-associated penetrating ocular trauma have an accompanying glass IOFB present, 6 which is related to shattering of tempered glass into polygonal fragments with sharp borders that can easily penetrate human tissue 3 , 6 .…”
Section: Introductionmentioning
confidence: 99%